Exploring Sibghah Meaning Difference: A Semantic Study towards the Al-Baqarah Verse 138 - Rizqi, Husain Miftahul (Journal of Language Intelligence and Culture, 2023)
This study aims to reveal the different meanings of the word ?ibgah in the Qur'an. The word ?ibgah is only once written in the Qur'an, which is located in surah Al-Baqarah verse 138. The word ?ibgah is analyzed using a semantic approach that is about changing meaning. The analysis was to investigate the meaning of ?ibgah according to the meaning of the Qur'an and then compare it with ?ibgah which is commonly understood today. The process of changing meaning and the types of changes in its meaning will be discussed. This type of research is library research by applying qualitative research. The data used in this study is the word ?ibgah in the Qur'an Surah Al-baqarah verse 138. The data collection technique is the documentation technique and the data collection method is the read and record method. The process of occurrence of such differences in meaning will be discussed and the types of changes in meaning displayed. The result of this study was that ?ibgah meanings differed between the meanings intended by the Qur'an and the meanings commonly understood today. The type of change in meaning found is the expansion of meaning.